Pathways to become a Qualified Accountant: A Comprehensive Guide for Students - Lim, Amy, Swee Geok (INTI International University, 2022)
Malaysian government targeted to have 60,000 qualified chartered accountants by year 2020. Dr Lim Swee Geok, also known as Dr. Amy Lim, the Chief Executive Officer of Ler Lum Advisory Services Sdn. Bhd. on the other hand, had a burning desire to provide comprehensive information on the various pathways leading to a chartered accountant qualification to students upon enrollment in tertiary education. Besides, there being no single book available as a point reference on the certification and the awarding professional bodies, with Dr. Amy’s desire crossing path with government’s direction, saw her in initiating an e-Book, ‘Pathways to Become a Qualified Accountant.’ Dr Amy holds a strong belief that every student, those pursuing an accounting degree, and those who are merely keen, deserves to bear sufficient knowledge on the available pathways to become a qualified accountant and by doing just that, they will be able to visualize clearly the paths that they intend to take, all whilst taking that step needed to reach, if not exceed, the government’s mission.